Estimation of errors by different lecurers - Krylovas, Aleksandras; Raulynaitis, Juozas; Subač, Olga (Lietuvos matematikos rinkinys, 2023)
Evaluation of students’ works where they present not only answer but solution also, can be subjective. In this article we present some exam tasks with non-correct solutions and statistics, that show wide evaluation scale dependingly on revising teacher.
Keywords: statistic education research; student achievement; mathematics teaching; measurement